Relation of Urinary pH and Specific Gravity with Urolithiasis, in Jalalabad, Nangarhar, Afghanistan - Ishaas, Toryalai; Azimee, M. Azim; Sherzad, Abdul Ghafar (International Journal For Research In Biology & Pharmacy, 2020)
Renal stone disease is, also known as Urolithiasis the most frequent recurrent urological problem-having worldwide distribution. Globally, urolithiasis is the third most common urological disease affecting both males and females. In developed countries, up to 12% of men and 7% of women will suffer from kidney stones in their lifetime, and the prevalence appears to be increasing. This retrospective descriptive study was conducted to determine the effects of urine pH and specific gravity in the formation of urinary stones among ultrasound confirmed Urolithiasis patients who reported to the Departments of Radiology and Biochemistry –Microbiology of Nangarhar Medical University Teaching hospital. Jalalabad, Afghanistan. Data on patient’s age, gender, seasonality, anatomical sites of the stone, biochemical parameters such as urine color, deposit, pH, specific gravity, Albumen, Glucose, Pus cells, Red Blood Cells (RBCs (and crystals were obtained from case records. Nonparametric Kruskal-Wallis test was used to find the mean of specific gravity and pH changed to anatomical location of stone and different seasons. Nonparametric Kruskal-Wallis test showed that there was no statistically significant difference in urine pH and specific gravity in patients with stones in different anatomical sites. On testing, the correlation between pH and specific gravity using spearman’s correlation test showed that there was no statistically significant correlation between pH and specific gravity in urine. The analysis of the effect of seasonality on specific gravity showed that specific gravity during the summer season was comparatively high compared to that in winter. The difference observed was not statistically significant. With regard to pH, during winter the mean pH was high when compared to that in summer. The difference observed was not statistically significant. Comparing specific gravity and pH, the highest mean specific gravity was observed in summer and the highest mean pH in winter. On comparing the mean specific gravity in crystalluric and non-crystalluric patients, an increasing trend was observed from urine with crystalluria. On comparing the mean pH with crystalluria a negative trend was observed, an increased pH for urine without crystals, and a decreased pH for urine with crystals urine.